Reliability and change in erosion measurements by high-resolution peripheral quantitative computed tomography in a longitudinal dataset of rheumatoid arthritis patients - Finzel, Stephanie; Manske, Sarah L.; Barnabe, Cheryl C.M.; Burghardt, Andrew J.; Marotte, Hubert; Scharmga, Andrea; Hauge, Ellen Margrethe; Chapurlat, Roland; Engelke, Klaus; Li, Xiaojuan; van Teeffelen, Bente C.J.; Conaghan, Philip G.; et al. (Journal of Rheumatology, 2021)
Objective. The aim of this multireader exercise was to assess the reliability and change over time of erosion measurements in patients with rheumatoid arthritis (RA) using high-resolution peripheral quantitative computed tomography (HR-pQCT). Methods. HR-pQCT scans of 23 patients with RA were assessed at baseline and 12 months. Four experienced readers examined the dorsal, palmar, radial, and ulnar surfaces of the metacarpal head (MH) and phalangeal base (PB) of the second and third digits, blinded to time order. In total, 368 surfaces (23 patients' 16 surfaces) were evaluated per timepoint to characterize cortical breaks as pathological (erosion) or physiological, and to quantify erosion width and depth. Reliability was evaluated by intraclass correlation coefficients (ICC), percentage agreement, and Light k; change over time was defined by means ± SD of erosion numbers and dimensions. Results. ICC for the mean measurements of width and depth of the pathological breaks ranged between 0.819-0.883, and 0.771-0.907, respectively. Most physiological cortical breaks were found at the palmar PB, whereas most pathological cortical breaks were located at the radial MH. There was a significant increase in both the numbers and the dimensions of erosions between baseline and follow-up (P = 0.0001 for erosion numbers, width, and depth in axial plane; P = 0.001 for depth in perpendicular plane). Conclusion. This exercise confirmed good reliability of HR-pQCT erosion measurements and their ability to detect change over time.
CRIS-Team Scopus Importer:2021-04-02
Keywords: Computed tomography; Metacarpophalangeal joint; Outcomes; Rheumatoid arthritis